Three years Experience in pancreaticoduodenectomies at a Department of Surgery - Huaraz, David (1998)
OBJECTIVE: To describe our experience in pancreaticoduodenectomies (Whipple resection) performed to resect a number of malignant diseases of the periampullary region, and the mortality as well as the operative time. MATERIALS AND METHODS: A single-institution (Hospital Nacional Almenara I.), retrospective review of the medical records from patients who underwent pancreaticoduodenectomy between 1994 and 1997 inclusive, was performed. RESULTS: We found 9 patients. whose mean age was 69 years, with 56% male and 44% female. The median operative time was 270 min (ranged from 360 to 720 min). Pathologic examination results showed periampullary adenocarcinoma of the head of the pancreas (66,7%, n=6), ampullary adenocarcinoma (11,1%, n=1), duodenal periampullary adenocarcinoma (interstitial tvpe) (11.1%), and distal bile duct primary adenocarcinoma (11,1%). The surgical technique performed was Whipple resection with end-to-side pancreatojejunal anastomosis (66,7%, n=6), end-to-side pancreatogastric anastomosis (22,214, n=2), and end-to-end pancreatojejunal anastomosis (11,1%, n=1). The surgical procedure involved pylorus preserving resection (modified Whipple resection) in 7 patients (77,8%), and the same without pylorus preservation (classic Whipple resection) ¡n the remaining two patients (22,2%). None of the patients required reoperation. The median postoperative length of stay was 2-5 days. Postoperative deaths were 2 (22,2%) within 30 days of operation. CONCLUSIONS: We performed mainly the modified Whipple resection pylorus preservation and pancreato.Key words: Pancreatectomy, adenocarcinoma, pancreas, periampular carcinoma; surgery operative.